Aesthetic pluralism - Villacañas Berlanga, Jose Luis (Estudios de Filosofía, 2008)
The age of the poets and the philosophy that was organized around it, have prepared the triumph of the image as the only form of criticism. Without a doubt, with this they have achieved the consumption of what can be as dense as time, the plurality that is plurality to the limit. There can be as much plurality as temporary instants are computable. Finally, the mimesis of time, the basic anthropological structure, can be in the hands of the human being, which is as much as having the capacity to produce oneself. We can already see what it means to eliminate all transcendence from oneself. With this, of course we have guaranteed pluralism, but only of a range of being: images. [Fragment]